PERBANDINGAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DAN TIPE JIGSAW PADA SISWA KELAS X DI SMA NEGERI 2 WAKORUMBA SELATAN KABUPATEN MUNA - Ety Nur Inah; Ratna Dewi (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2015)
AbstractThis paper adresses the learning outcomes of Islamic educat ion lesson in cooperative learning model between the type of teams games tournament (TGT) and the type of Jigsaw for students of class X at SMA 2 in south Wakorumba Muna regency. The issues were examined in this study whether there are difference in learning out comes in cooperative learning model  between the t ype teams games tournament (TGT) and the t ype of Jigsaw instudy Islamic educat ion. In this paper, the author uses data collection techniques by dcumentation and the test result study with quantitative method. The population of this study is all the students of class X at SMA 2 at south wakorumba. Sampling technique using a random sampling which is taken two classes in class X 1 through cooperative learning model using teams games tournament (TGT) as class A treatment and the students of class X3 as a class B treatment using Jigsaw model. The results of thestudents learning through cooperative learning model, show the maximum value  is 97 and the minimum value is 77, (X)=86,84, varians (S)=32,63 and a standard deviation (S) = 5,38. The results study of islamic religious education through cooperative learnimg model of jigsaw, shows a maximum value is 90 and a minimum value is 70, the average (X)=78,54, varians (S2)=26,24 and the standard deviation (S) = 5,04. Testing the hypothesis used t-test and obtained t = 5,09 >  = 1,68. Then, the hypothesisreject H o counting or accept H. This shows that the use of cooperativelearning model teams games tournament improve learning outcomes of islamic education lesson rather than using the cooperative learning model of jigsaw.                                     Keyword: learning outcomes, Islamic education lesson, cooperative a learning model, type teams games tournament (TGT), cooperative learning model of jigsaw.Abstrak Penelit ian ini membahas masalah perbandingan hasil belajar Pendidikan Agama Islam melalui model pembelajaran koopratif t ipe Teams Games Tournament (TGT) dan tipe Jigsaw pada Siswa kelas X di SMA Negeri 2 Wakorumba Selatan Kabupaten Muna. Yang dikaji dalam penelit ian ini adalah apakah ada perbedaan hasil belajar siswa melalui model pembelajaran kooperatif  t ipe TGT dan t ipe Jigsaw pada bidang studi Pendidikan Agama Islam. Dalam penelit ian ini, penulis menggunakan teknik pengumpulan data dokumentasi dan tes hasil belajar dengan metode pengolahan data kuant itatif. Populasi dalam penelit ian ini adalah seluruh siswa kelas X di SMA Negeri 2 Wakorumba Selatan. Teknik pengambilan sampel menggunakan Random Sampling, sampel sebanyak 2 kelas yaitu siswa kelas X1 sebagai kelas perlakuan A melalui model pembelajaran kooperatif t ipe TGT dan siswa kelas X3 sebagai kelas perlakuan B melalui model pembelajaran kooperatif t ipe Jigsaw. Berdasarkan hasil analisis deskriptif, hasil belajar siswa melalui model pembelajaran kooperatif t ipe TGT menunjukkan nilai maksimum 97 dan nilai minimum 77, (X)=86,84, varians (S2)=32,63 dan standar deviasi (S) = 5,38. Hasil belajar Pendidikan Agama Islam siswa melalui model pembelajaran kooperatif t ipe Jigsaw menunjukkan nilai maksimum 90 dan nilai minimum 70, rata-rata (X)=78,54, varians (S2)=26,24 dan standar deviasi (S) = 5,04. Pengujian hipotesis digunakan uji-t, dan diperoleh  = 5,09 >  = 1,68. Maka, hipotesis menolak  atau menerima . Hal ini menunjukkan bahwa penggunaan model pembelajaran kooperatif tipe TGT lebih meningkatkan hasil belajar Pendidikan Agama Islam daripada penggunaan model pembelajaran kooperatif tipe Jigsaw.Kata Kunci:  Hasil belajar Pendidikan Agama Islam, model pembelajaran  kooperatif tipe Teams Games Tournament(TGT), model pembelajaran kooperatif tipe Jigsaw.